THE IMPACT OF PHYSICAL WORK ENVIRONMENT TOWARD EMPLOYEE PERFORMANCE AT PT. BANK NEGARA INDONESIA MANADO REGIONAL OFFICE - Rorong, Syutrika Vergie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Physical work environment is one of the essential human requirements that enable people to perform their work effectively under defined conditions. It is the quality of the employee’s workplace environment that has most influence on the level of employee’s motivation and subsequent performance. Research sought to understand the influence of physical work environment on employees’ performance. Population this research is the employees of PT. Bank Negara Indonesia Manado Regional Office with sample as many as 29 respondents. Data analysis was Simple Linear Regression Analysis and the instrument of data collection was structured questionnaires for the top level managers and lower level employees. Research concludes that there is a significant effect of Physical Work Environment on Employee Performance. To ensure productivity of employees, management needs to pay attention to the Physical Work Environment so that employees feel comfortable and happy to work in the company. Keywords: physical work environment, employee performance